The Influence of Social Media, Financial Literacy and Quality of Information on Students' Interest in Investing In The Capital Market - Putri, Hana Tamara; Ahmadi, Ahmadi; Mutiqum, Rabia Surya Mauna (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the effects of social media, financial literacy, and the quality of information on students' investment interest in the capital market. The research method used is descriptive and quantitative analysis. The data used is primary data. The population in this study consists of students at Jambi University. The analytical techniques include simple regression analysis, hypothesis testing, correlation, determination coefficient, and t-test. Jambi University is one of the public universities in Jambi Province. It is the oldest public university, established in March 1963, and currently has nine faculties and ninety-two study programs. The results show that the independent variables (social media, financial literacy, and quality of information) significantly and simultaneously affect the dependent variable (investment interest). Furthermore, the independent variables can explain 89.3% of the influence on the dependent variable, with a determination coefficient (R²) of 0.893. In conclusion, social media, financial literacy, and quality of information significantly influence investment interest.